Perceptions journal of international affairs
Perceptions is a quarterly English language academic journal that features contributions from distinguished Turkish and international scholars. Perceptions is the flagship publication of SAM. The content of the journal ranges from security and democracy to conflict resolutions and international challenges and opportunities.